USING EXISTING PAEDIATRIC PRE-HOSPITAL TRAUMA TRIAGE TOOLS TO IDENTIFY CHILDREN WITH SEVERE TRAUMATIC BRAIN INJURY–AN ANALYSIS OF NATIONAL TRAUMA REGISTRY DATA. Issue 10 (7th September 2013) - Lyttle, M D; Ardolino, A; Berry, K; Bouamra, O; Cheung, R; Lawrence, T; Lecky, F; Maconochie, I K
Abstract : Objectives & Background: Severe traumatic brain injury (TBI) in childhood causes long term neurodisability and death, though early neurosurgical intervention may improve outcome. Primary transfer to a neurosurgical centre reduces the time from initial Emergency Department arrival to performance of time critical procedures. Paediatric trauma and neurosurgery services in England have recently undergone reconfiguration. To assist pre-hospital clinicians in determining the most suitable destination for an injured child a number of trauma triage tools have been developed. We aimed to assess the performance of these tools in identifying children with severe TBI. Methods: Eight paediatric pre-hospital trauma triage tools were identified via survey and literature review. Retrospective clinical registry data for children <16 years were obtained from the Trauma Audit and Research Network during 2007–2012. Severe TBI was defined as Abbreviated Injury Score ≥3 in the head region as less severe injuries are unlikely to require neurosurgery. Performance of the tools in identifying severe TBI was assessed, with clinically acceptable cut-offs for under and over-triage assigned at the level of ≤5% and ≤50% respectively. Results: 338 (30%) of 1118 patients had severe TBI. None of the tools demonstrated an acceptable under-triage rate (range 7–68%). Two had acceptable over-triage rates of 90% and 82%, though these displayed the highest rates of under-triage. The remaining tools had over-triage rates of 56–83%. Conclusion: None of the existing paediatric pre-hospital trauma triage tools perform adequately in identifying severe TBI. Given the incidence of severe TBI in this population, and the benefits of appropriate disposition, any such tools subsequently derived should pay particular attention to their performance in regard to severe TBI with particular focus on optimising under triage rates.